AUDIT MANAJEMEN TERHADAP PENGELOLAAN FUNGSI SUMBER DAYA MANUSIA (STUDI KASUS PADA PT. BANK PEMBANGUNAN DAERAH JAMBI PERIODE 2015) - Amini, Muhammad Raviki; Hariyanto, Joko; Tri Wulandari, Venda (LPPM Universitasdiwangsa Jambi, 2018)
The purpose of this study was to determine whether PT. Bank Pembangunan DaerahJambi has implemented the Human Resources function in accordance with theexisting provisions, and to determine whether the Audit Human ResourceManagement could improve performance and could run human Resources Taskeffectively. To show that a management audit can be used to assess the effectivenessof the HR function by comparing the fit between the company's policy that has beendetermined by the actual implementation. The method used in this research is descriptive qualitative method in which data is collected, compiled, interpreted and analyzed, and then compared with existing theories. To produce a good method inmaking decision is used two types of data, primary data and secondary data, as wellas data collection techniques used through the preliminary surveys, field studies byobservation, interviews and documentation, as well as the study of literature. Theresults of Audit Management show that the Human Resources management not runeffectively yet, because there are still some weaknesses in the management of humanresources at PT Bank Pembangunan Daerah Jambi. The weaknesses can be seen inthe organizational structure, not good human resource planning, in the analysis ofthe needs of employees, in the recruitment, in the selection, training and developmentof employees. Based on the above weaknesses the author recommended that the BankPembangunan Daerah Jambi; to comply the empty job in the organization structure, planning appropriate human resources for each year, recruiting human resourcesaccording to the needs and improving the analysis of the needs of employees,selecting human Resources according to the Manual book of human resources,improving human Resources training and development fit with types of relevanttraining of each fields competency